Morbidity, Growth and Food Intake among the Underfives in Madura, Indonesia - Sri Kardjati; Jane A. Kusin; Wilm van Steenbergen; W. N. Schofield (Indonesian Pediatric Society, 1992)
The relation between common illnesses, growth and breast milk and food intake was assessed in a-longitudinal population based study, covering 300 children, age 0-36 months. Morbidity was quite prevalent with a peak at age 4-24 months. It did, however, not affect the intake of breast milk and the consumption of additional foods in infancy. On the other hand, the daily intake of energy and protein was significantly reduced in older and particularly non-breastfed children. Morbidity explained about 28% of the variance in weight- and height-for-age in children, age 6-18 months. One can conclude that growth faltering early in infancy is primarily of nutritional origin, while at older age it is due to a synergistic effect of inadequate nutrition and morbidity. Anorexia rather than bad feeding habits is the main cause of poor dietary intake during and after illness.